Sustainability Marketing- A New Approach in Marketing - Varghese, Sony (European Economic Letters (EEL), 2023)
Sustainability marketing is a commercial approach that tries to advertise and sell products and services while reducing negative effects on the environment and society. To take this tack, businesses must adopt eco-friendly procedures across the board and let their customers know about it. If businesses are serious about sustainability, they need to promote sustainable practises among their customers as well as within the company itself. Sustainability marketing is becoming increasingly important to businesses as people become increasingly conscientious about the effects of their purchases on the world around them.